Mini review of plant products as food supplement against MSG-induced liver injury: antioxidant, oxidative stress and histological prospects - Kasmara, Dwi Pratiwi; Abdullah, Erlina; Harun, Zaliha; Sari, Fatmi Nirmala; Abd Rashid, Norhashima; Teoh, Seong Lin (Frontiers in Pharmacology, 2025)
Monosodium glutamate (MSG) is an odorless white solid crystalline derived from the amino acid glutamic acid. It is widely used as a flavor enhancer, but its excessive consumption has been associated with toxicity to various organs. In MSG-induced liver injury, few mechanisms have been identified, which started with the generation of reactive oxygen species that leads to oxidative stress which further causes liver injury. In response to this health concern, there is growing interest in various plant products such as plant extracts, flavonoids and phenolic compounds that were able to minimize oxidative stress, serum transaminases and scavenge free radicals in the liver after MSG administration. This review explores the potential of various plant products as dietary supplements to MSG-induced liver injury, focusing on their antioxidant activities, modulatory effects on liver function markers, and histological outcomes. By compiling this evidence, this review provides insights into their potential as preventive strategies against MSG-related liver toxicity, supporting their inclusion in dietary regimens for the maintenance of liver function.